Machine Learning and Software Engineering in Health Informatics - Clifton, D; Gibbons, J; Davies, J; Tarassenko, L (2012)
Health informatics is a field in which the disciplines of software engineering and machine learning necessarily co-exist. This discussion paper considers the interaction of software engineering and machine learning, set within the context of health informatics, where the scale of clinical practice requires new engineering approaches from both disciplines. We introduce applications implemented in large on-going research programmes undertaken between the Departments of Engineering Science and Computer Science at Oxford University, the Oxford University Hospitals NHS Trust, and the Guy’s and St Thomas’ NHS Foundation Trust, London.